Green Accounting From The Perspective Of Micro, Small, and Medium-Sized Enterprises (Msmes) - Nur Jannah; Marwah Yusuf; Nuramal Nuramal (JURNAL ECONOMINA, 2026)
This study aims to understand the perspectives of Micro, Small, and Medium Enterprises (MSMEs) on the implementation of green accounting in their business activities. This study employs a qualitative approach using an interpretive paradigm and phenomenological methods. This approach was chosen to deeply explore the experiences, views, and meanings constructed by MSME operators regarding green accounting practices in their business activities. Data were collected through in-depth interviews, observations, and documentation of MSME operators in Makassar City across various business sectors. The results indicate that most MSME operators have an initial awareness of the importance of environmental conservation but do not yet fully understand the formal concept of green accounting. The practices they employ are generally still simple, such as waste management and efficient use of raw materials, without integrated recording in financial statements. The main obstacles faced include limited knowledge, a lack of clear regulations, and limited resources. Nevertheless, MSME operators believe that the implementation of green accounting has the potential to provide economic benefits, enhance business reputation, and support business sustainability. This study concludes that a green accounting model that is simple, practical, and tailored to the characteristics of MSMEs is needed so that it can be effectively implemented.